Pengaruh Psychological Capital Dan Stres Kerja Terhadap Turnover Intention - Haura, Alya Al; Mardhiyah, Ainun (Jurnal Ilmiah Wahana Pendidikan, 2025)
The millennial generation is one of the workforce positions that continues to increase in number. This generation will change jobs on average twenty times during their lifetime, compared with traditionalists who work for the same employer until they retire. The creation of effective psychological capital will help reduce the level of employee desire to move, as well as decreasing the stress level in employees will reduce the employee's desire to leave the company. This research aims to analyze "The Effect of Psychological Capital and Job Stress on Turnover Intention (Study of Millennial Generation Employee PT. PLN (Persero) UP3 Medan). The influence between psychological capital and work stress will be analyzed partially and simultaneously on turnover intention. This research is in the form of a survey by distributing offline questionnaires to 59 employees of PT. PLN (Persero) UP3 Medan, which belongs to the millennial generation using a Likert scale. he data collection method was carried out within 1 month from March to April 2024. The sampling technique is saturated sampling. The data analysis technique used instrument test of reliability validity, classical assumption test, hypothesis test using multiple linear regression analysis using SPSS. The results of the research show that psychological capital has a significant negative effect on turnover intention. This shows that the higher the psychological capital an employee has, the lower turnover intention will be. Other results show that job stress has a significant positive effect on turnover intention.